Interaction Between Neurogenic Stimuli and the Gene Network Controlling the Activation of Stem Cells of the Adult Neurogenic Niches, in Physiological and Pathological Conditions - Ceccarelli, Manuela; D’Andrea, Giorgio; Micheli, Laura; Tirone, Felice (Frontiers in Cell and Developmental Biology, 2020)
In the adult mammalian brain new neurons are continuously generated throughout life in two niches, the dentate gyrus of the hippocampus and the subventricular zone. This process, called adult neurogenesis, starts from stem cells, which are activated and enter the cell cycle. The proliferative capability of stem cells progressively decreases during aging. The population of stem cells is generally quiescent, and it is not clear whether the potential for stem cells to expand is limited, or whether they can expand and then return to quiescence, remaining available for further activation. Certain conditions may deregulate stem cells quiescence and self-renewal. In fact we discuss the possibility of activation of stem cells by neurogenic stimuli as a function of the intensity of the stimulus (i.e., whether this is physiological or pathological), and of the deregulation of the system, (i.e., whether the model is aged or carrying genetic mutations in the gene network controlling quiescence). It appears that when the system is aged and/or carrying mutations of quiescence-maintaining genes, preservation of the quiescent state of stem cells is more critical and stem cells can be activated by a neurogenic stimulus which is ineffective in normal conditions. Moreover, when a neurogenic stimulus is in itself a cause of brain damage (e.g., kainic acid treatment) the activation of stem cells occurs bypassing any inhibitory control. Plausibly, with strong neurogenic stimuli, such as kainic acid injected into the dentate gyrus, the self-renewal capacity of stem cells may undergo rapid exhaustion. However, the self-renewal capability of stem cells persists when normal stimuli are elicited in the presence of a mutation of one of the quiescence-maintaining genes, such as p16Ink4a, p21Cip1 or Btg1. In this case, stem cells become promptly activated by a neurogenic stimulus even during aging. This indicates that stem cells retain a high proliferative capability and plasticity, and suggests that stem cells are protected against the response to stimulus and are resilient to exhaustion. It will be interesting to assess at which functional degree of deregulation of the quiescence-maintaining system, stem cells will remain responsive to repeated neurogenic stimuli without undergoing exhaustion of their pool.